Association of Human Leukocyte Antigen (HLA) Class II Alleles of DQB1 (DQB1*03:02) (DQB1*06:02) and DRB1 (DRB1*04:01) with Type-1 Diabetes Patients of Khyber Pakhtunkhwa, Pakistan (Molecular Medicine Communications, 2024)
Type-1 diabetes (T1D), an autoimmune disease, significantly impacts global health, with varying prevalence across different geographies. This study investigates the association of specific Human Leukocyte Antigen (HLA) Class II alleles, namely DQB1*03:02, DQB1*06:02, and DRB1*04:01, with T1D in the Khyber Pakhtunkhwa (KP) population of Pakistan. Conducted as a 1:1 matched case-control study, this research involved 33 T1D patients and an equal number of age- and gender-matched healthy controls. Our findings reveal a weak association of alleles DRB1*04:01 and DQB1*03:02 with T1D (OR = 2.065 and 1.393, respectively, p > 0.05). DQB1*06:02 allele, which is considered to have a protective effect against T1D was more prevalent in control as compared to cases (93.9% vs 90.9%), however, the association was non-significant (OR 0.645, p > 0.05).  These insights contribute to understanding genetic influences on T1D in the KP region and underscore the need for further research with larger, diverse cohorts to refine the genetic markers of T1D risk and protection
Keywords: Type 1 Diabetes; HLA Class II; Genetic Association; Polymorphism; Genomic Ethnicity